Analisis Kualitatif Terhadap Pandangan Kumaila Tentang Konsumsi Daging Babi dalam Diskursus Islam Perspektif Ulama Tradisional - Mahfud, Ahmad; Hamidah, Nurul; Mahmud, Surya Saputra; Yardho, Moh. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This research discusses issues related to the controversy over the law of consuming pork in Islam, triggered by Kumaila's views in a YouTube video, which has caused debate among the public and necessitates an in-depth analysis to understand Kumaila's arguments. The purpose of this research is to criticize scientific arguments related to the law of consuming pork in Islam and analyze Kumaila's views on pork through the video